The Positive Impact of Play Therapy on Writing Performance of Students With Dysgraphia - Shadie Khaledi; Azar Validi Pak; Iraj Mirkhan; Marzie Atai (Shiraz University of Medical Sciences, 2014)
Background: The writing language is learned in the hierarchy of children's ability after the listening, speaking and reading and therefore, any problems in other areas such as listening, speaking and reading can have a negative impact on language learning. Over the years, there were many ways to treat this disorder, including play therapy which has been used in various fields to combat learning disorders. Objectives: The purpose of the present study was to investigate the effect of play therapy on writing performance of students with dysgraphia. Materials and Methods: This is a quasi-experimental study comprising pretest-posttest with control group. The Wechsler Intelligence test, writing and spelling errors assessment scale were used on 30 first- grade students with dysgraphia in the center of learning disorders in Marivan. The pupils were randomly divided into experimental and control groups, each containing 15 students. The experimental group attended 14 play therapy training sessions in 2 months. Results: Results revealed that play therapy had significantly positive impact on writing performance of experimental students compared to control group. Conclusions: Improvement of writing performance in students with dysgraphia revealed reduction of spelling errors. This intervention may help experimental group overcome their writing difficulties, purposefully perform their activity, and to achieve correct spelling of words.